Assessment of exposure to MRI motion‐induced fields based on the International Commission on Non‐Ionizing Radiation Protection (ICNIRP) guidelines. Issue 4 (3rd November 2015) - Zilberti, Luca; Bottauscio, Oriano; Chiampi, Mario
Abstract : Purpose: The goal of this study was to conduct an exposure assessment for workers moving through the stray stationary field of common MRI scanners, performed according to the recent International Commission on Non‐Ionizing Radiation Protection (ICNIRP) Guidelines, which aim at avoiding annoying sensory effects. Theory and Methods: The analysis was performed through numerical simulations, using a high‐resolution anatomical model that moved along realistic trajectories in proximity to a tubular and open MRI scanner. Both dosimetric indexes indicated by ICNIRP (maximum variation of the magnetic flux density vector and exposure index for the motion‐induced electric field) were computed for three statures of the human model. Results: A total of 51 exposure situations were analyzed. None of them exceeded the limit for the maximum variation of the magnetic flux density, whereas some critical cases were found when computing the induced electric field. In the latter case, the exposure indexes computed via Fourier transform and through an equivalent filter result to be consistent. Conclusion: The results suggest the adoption of some simple precautionary rules, useful when sensory effects experienced by an operator could reflect upon the patient's safety. Moreover, some open issues regarding the quantification of motion‐induced fields are highlighted, putting in evidence the need for clarification at standardization level. Magn Reson Med 76:1291–1300, 2016. © 2015 Wiley Periodicals, Inc.